Cake formation of bidisperse suspensions in dead-end microfiltration - Han, Qi (2021)
The evolution of the cake during dead-end microfiltration of different compositions of bidisperse feeds was investigated using network modeling and three-dimensional (3D) optical coherence tomography (OCT) imaging. The foulant particles were latex of two different sizes (namely, 3 and 5 µm) and the membrane was polycarbonate track-etched with nominal diameter of 2 µm. The results from the network model indicate that (i) the deposition of the smaller particles on the non-porous area was reduced by the presence of larger particles, whereas that of the larger particles was not affected by the concentration of the smaller ones; and (ii) monodisperse small particles gave a greater specific cake resistance than monodisperse large particles, and the specific cake resistance of the bidisperse mixture can only be reduced with a sufficient proportion of larger particles. OCT results substantiated the model by revealing that (i) bidisperse feeds tended to form homogeneous cakes, but the presence of a higher concentration of large particles led to heterogeneous cakes; (ii) the presence of a lower concentration of larger particles enhanced clustering, while a higher concentration reduced that; and (iii) in the longer-term filtration, the monodisperse feed of small particles dynamically deposited and detach continuously, while the bidisperse feed with the highest concentration of larger particles exhibited negligible deposition and detachment.